Y=log1/3 (3-1)

# G(x)=log(x-3) Description Of Transformation: Equation(s) For The Vertical Asymptote(s): X-intercept In (x, Y) Form: Can You Help?

Log[x]4x=5(log[x]x-log[c]y)

F(x) = log x

x = 0

x intercept: (1, 0)

g(x) = log(x-3)

Log (x-3) just moves the graph to the 3 units right, so the new vertical asymptote is, in place of (1, 0) is

x intercept: (4,0)

x = 0

x intercept: (1, 0)

g(x) = log(x-3)

Log (x-3) just moves the graph to the 3 units right, so the new vertical asymptote is, in place of (1, 0) is

x intercept: (4,0)